The Effect of Breastfeeding Technique Education on the Breastfeeding Efficacy of Public Mothers at the GSIA Nabire Clinic, Papua - Elisabeth Bunapa; Tuti Yanuarti (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2022)
Aims: To assess the effect of breastfeeding technique education on the effectiveness of postpartum mothers in breastfeeding Methods: Quasi-experimental with one group pre-test-post-test design. The sample in this study were all primiparous postpartum mothers at the GSIA Clinic from January - to March 2022, as many as 30 people (purposive sampling). Results:    The effectiveness of postpartum mothers in breastfeeding before being given breastfeeding technique education was primarily a sufficient level of 76.7%, and after breastfeeding was mostly a good level of 53.3%. There is an effect of education on breastfeeding techniques on the effectiveness of postpartum mothers in breastfeeding (p.value 0.000). Conclusion:    There is an effect of education on breastfeeding techniques on the effectiveness of postpartum mothers in breastfeeding.